2022
DOI: 10.1007/s40808-022-01352-3
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observations for monitoring atmospheric NO2 in correlation with the existing pollution sources under arid environment

Abstract: Monitoring of air pollutants using satellite data has been largely improved over the past few decades, which can provide deeper insights into the effects of anthropogenic activities on the air quality. The observations and measurements of atmospheric NO 2 are poorly investigated in North Africa, therefore, the current study applied a multi-proxy approach to better understand of the ambient environment. This approach is based on satellite observations, chemical and biological analyses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This may be related to human activity and NO 2 emissions in the streets 28 . Study has shown that NO 2 emissions generally peak in the summer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to human activity and NO 2 emissions in the streets 28 . Study has shown that NO 2 emissions generally peak in the summer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The ESA WorldCover 2020 product (https://worldcover2020.esa.int/downloader), accessed on 25 September 2021, has recently been utilized in studies such as those by Ekim et al [45]; Salama et al [47] and Tavus et al [48]. The product was based on Sentinel-1 and Sentinel-2 satellite data acquired in 2020 and derived 11 generic land-cover classes at a 10 m spatial resolution, with an overall accuracy of 74% at the global level and 81% at the Asia level [49].…”
Section: Land-use/cover Datamentioning
confidence: 99%
“…Thus, in addition to interest in developing denitrification technologies to decrease NO x emissions, 27 an appropriate understanding and inclusion of NO x chemistry in large-scale weather, air quality and climate models are necessary to alleviate discrepancies between observations and predictions, especially regarding ROS concentrations in the atmosphere. 10,16 Indeed, nitrogen-based ROS have been detected by satellites in NO 2 -polluted and arid areas 28 and by the results of NO 2 chemistry related to biogenic volatile compounds. 29 NO 2 chemistry has also recently been used to explain haze formation in highly polluted areas.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The chemistry of NO 2 is a key factor in controlling the oxidizing power of the atmosphere. Thus, in addition to interest in developing denitrification technologies to decrease NO x emissions, an appropriate understanding and inclusion of NO x chemistry in large-scale weather, air quality and climate models are necessary to alleviate discrepancies between observations and predictions, especially regarding ROS concentrations in the atmosphere. , Indeed, nitrogen-based ROS have been detected by satellites in NO 2 -polluted and arid areas and by the results of NO 2 chemistry related to biogenic volatile compounds . NO 2 chemistry has also recently been used to explain haze formation in highly polluted areas. , In the specific case of NO 2 chemistry, our group has recently suggested a novel chemical pathway by which NO 2 can be adsorbed on a poorly hydrated silica surface and chemically converted into ROS (HONO and OH radicals) without any NO 2 dimerization (i.e., ).…”
Section: Introductionmentioning
confidence: 99%